CRITICAL LITERACY, RESIGNIFICATION OF READING IN ENGLISH LANGUAGE AND RESCUE OF CITIZENSHIP - Ilza Léia Ramos Arouche (Revista Eletrônica Científica Ensino Interdisciplinar, 2020)
This study is directed to describe and analyze two literacy events from the narratives in the university context to understand how literacy and resignification of reading in Foreign Language occur. Therefore, the objective is to provide literate practices based on the tales of local writers and to promote citizenship and rescue local culture. The scientific work was supported by a qualitative interpretive research of an ethnographic value that was configured in interventional action research and integrated a master's project in applied linguistics, and then a doctorate. The instruments were elaborated according to the researched context, in this section was the descriptive memorial. The research shows that events of critical literacy in English from a social perspective supported by the genre short stories can favor literate practices based on the tales of local writers and foster citizenship and rescue local culture.